A comparative study among stakeholders on causes of time delay in Malaysian multiple design and build projects - Ramanathan, C.T. (IEEE Computer Society, 2014)
The construction industry plays an important role in developing a nation to a fully developed status. The construction industry, unlike other industries has unique problems concerning project completion. Projects are now more complicated involving huge contract values, participants from multi-discipline, more specialised works, tighter schedule, more cost consciousness, stringent quality standards, etc. Ultimately, cost and time are the two key parameters that play significant role in construction project management. In Malaysia very few studies have been attempted on the factors causing time delay. Besides, there has been no such study related to multiple Design and Build (DandB) projects. The study focused on DandB projects which have complicated risk governed with fixed time and a fixed contract sum (Lump sum). Thus there is a need for comparative study on the risk factors causing this time delay which enables the Malaysian construction to respond proactively and more effectively to time delay factors. Â© 2014 IEEE.